2023
DOI: 10.1186/s13550-023-00952-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the radiation dosimetry protocol in Lutetium-177-PSMA therapy: toward clinical implementation

Abstract: Background Dosimetry in [177Lu]Lu-PSMA therapy is a valuable tool to assess treatment efficacy and toxicity. This study aims to develop a clinically implementable protocol to determine the absorbed dose in organs and tumor lesions after [177Lu]Lu-PSMA-617 therapy, by reducing the imaging time points and utilizing population-based kinetics with a single scan, with evaluation of its influence on the uncertainty in absorbed dose. Methods Ten patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
3
14
2
Order By: Relevance
“…This was recently supported by retrospective work from Schuchardt et al showing a significant difference in kidney absorbed dose between these two compounds (0.77 Gy/GBq for [ 177 Lu]Lu-PSMA-617 vs. 0.92 Gy/GBq for 177 Lu-PSMA-I&T, P = 0.0015) [16]. However, this retrospective study is impaired by its alternating dosimetry protocol and by relying on planar imaging, which can significantly affect the accuracy of the dosimetry outcomes [23][24][25]. With our results using an elaborate and identical dosimetry protocol, we can confirm the previous preclinical and retrospective study outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…This was recently supported by retrospective work from Schuchardt et al showing a significant difference in kidney absorbed dose between these two compounds (0.77 Gy/GBq for [ 177 Lu]Lu-PSMA-617 vs. 0.92 Gy/GBq for 177 Lu-PSMA-I&T, P = 0.0015) [16]. However, this retrospective study is impaired by its alternating dosimetry protocol and by relying on planar imaging, which can significantly affect the accuracy of the dosimetry outcomes [23][24][25]. With our results using an elaborate and identical dosimetry protocol, we can confirm the previous preclinical and retrospective study outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…and one late time point (7 days p.i.) [ 19 ]. Since this would therefore be a suitable protocol for clinical routine, it was evaluated whether bone marrow dosimetry based on a SPECT/CT scan at 24 h and 7 days would be comparable to 5-time-point dosimetry.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, for clinical implementation, we investigated the possibility to limit the number of time points for bone marrow dosimetry. For other organs at risk (kidneys, salivary glands) and lesions it has been suggested that one or two imaging time points are sufficient to reliably calculate the absorbed dose [ 19 21 ]. Therefore, it would be practically convenient if these images could also be used to calculate the bone marrow absorbed dose.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MRI examinations are expensive, noisy, and time-consuming and, furthermore, they are unsuitable for patients with metal implants (Table 1) [43]. [7,[36][37][38][39][40][41][42][43][44][45][46]. Effective combining noninvasive, real-time, dynamic, and quantitative radiation imaging with radiation therapy has become a popular strategy for molecular imaging-guided precise treatment (Table 1).…”
Section: Technologiesmentioning
confidence: 99%
“…In particular, PET with 68 Ga labeled diagnostic reagents is used for patient selection and efficacy evaluation, while SPECT is used to evaluate the dynamic distribution and stability of 177 Lu labeled single-photon therapy drugs in vivo. For example, the FDA has approved 177 Lu-PSMA-617 (Pluvicto) for the treatment of prostate-specific membrane antigen (PSMA)-positive metastatic castration-resistant prostate cancer and 68 Ga-PSMA-11 for the selection of patients who can be treated with Pluvicto and for post administration efficacy evaluation [45,46]. The half-life of PET diagnostic reagents is relatively short, which is beneficial for reducing radiation damage to the body but unfavorable for evaluating the dynamic distribution and stability of radiation therapy drugs (with a half-life of a few days to achieve therapeutic effects) in vivo.…”
Section: Technologiesmentioning
confidence: 99%